Leitura como atividade dialógica e seu processo de ensino-aprendizagem : um projeto com o gênero história em quadrinhos - Remonatto, Angélica (2013)
This study intends to investigate and discuss the reading practices and the teaching-learning process of students in the 6th grade of elementary school in a Brazilian public school. To this end, we used the theory of Mikhail Bakhtin and his Circle (1929; 1952-53; 1970-1971/1979; 1974/1979), that considers language as process social-cultural-historical, allied to social-interactional theory of teaching-learning of Lev Vygotsky (1930, 1934). Based on such perspectives, we form our conception of reading in a dialogical approach, providing for a responsive attitude of the reader. Thus, we investigated what practices have been developed for effective learning of that important curricular component. We argue that the discourse genres can be used as objects of teaching-learning of the reading and we also believe the formation of readers is a process that should occur during every school year and not only in the first years. The methodology approach has been based on a qualitative study, participative and dialogic character. The data showed that the interaction and knowledge of the genre "comics" could offer news possibilities of reading and the development of different capabilities by the students. Our data also demonstrated that the teaching-learning of reading becomes even most proficient when allied to activities of reflection and written production.